2006
DOI: 10.1299/jsmeb.49.941
|View full text |Cite
|
Sign up to set email alerts
|

Toward Smart Control of Turbulent Jet Mixing and Combustion

Abstract: Recent progress in active control of jet mixing and combustion is introduced. Miniature electromagnetic flap actuators are mounted on the periphery of an axisymmetric nozzle exit. It is demonstrated that even weak disturbances introduced into the initial shear layer by these actuators can significantly modify the large-scale vortical structures. This control technique is extended to the control of methane/air mixing and diffusion combustion by using a coaxial jet nozzle with the same flap actuators. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A control must interact with turbulent fluctuations in a jet, and the random aspects of the fluctuations reduce the effectiveness of an open-loop control. The sensor-feedback or closed loop may treat effectively the random-phase problem in turbulence dynamics (Bushnell and Mcginley 1989;Zhang et al 2004) and allow flexibly controlled jet mixing (Kasagi 2006). The latter is important since the optimal control configuration for jet mixing varies with the operating conditions such as Mach number and temperature ratio.…”
Section: Introductionmentioning
confidence: 99%
“…A control must interact with turbulent fluctuations in a jet, and the random aspects of the fluctuations reduce the effectiveness of an open-loop control. The sensor-feedback or closed loop may treat effectively the random-phase problem in turbulence dynamics (Bushnell and Mcginley 1989;Zhang et al 2004) and allow flexibly controlled jet mixing (Kasagi 2006). The latter is important since the optimal control configuration for jet mixing varies with the operating conditions such as Mach number and temperature ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Passive flow control is effective and economical control method, however it is important to know the flow characteristics well and use it because the flow situation changes largely with a slight change in the shape of flow (a) Axisymmetric nozzle with arrayed 18 electromagnetic flap actuators Fig. 33 Jet bifurcation induced by the actuation of alternate mode at St = 0.25 (by Suzuki et al, 2004, Kasagi, 2006 (b) Visualized flow pattern Shakouchi, Mechanical Engineering Reviews, Vol.7, No.1 (2020) [DOI: 10.1299/mer.19-00386] passage. As mentioned above, in this paper, passive flow control of jets flows were mainly examined, however, active flow control is also very important because passive flow control method is useful but its effectiveness is limited.…”
Section: Resultsmentioning
confidence: 99%
“…The induced flow can be used to control the main flow. * active flow control by intelligent nozzle: Suzuki et al (2004), Kurimoto et al (2004) and Kasagi (2006) demonstrated the active jet flow control by an intelligent nozzle with 18 electromagnetic flap actuators as shown in Fig. 33(a).…”
Section: Active Jet Flow Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…This reorientation of structures through mutual induction was demonstrated through a series of vortex filament simulations, which are described in Leonard (1985). Similar dynamics has also been produced by employing alternative methods of active forcing (Suzuki, Kasagi & Suzuki 2004; Kasagi 2006) or passive control (Longmire & Duong 1996).…”
Section: Introductionmentioning
confidence: 90%